2018
DOI: 10.1080/07036337.2018.1546302
|View full text |Cite
|
Sign up to set email alerts
|

Knowing is not loving: media effects on knowledge about and attitudes toward the EU

Abstract: Media provide the public with information related to the European Union which may alter individuals' perceptions, ultimately resulting in changes in performance evaluations of the EU. Knowledge gains may be an important mediator in this process. We present data from a study in the context of the 2016 Bratislava summit in which the Heads of the Union's governments discussed the outcome of the Brexit vote and the EU's future. A panel survey assessed the relationship between exposure to media content, event-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…For the actual expectation of a media effect on the individual level, we follow the straightforward argument by Hobolt and Tilley (2014) that news media can have effects on responsibility beyond framing, and in particular on the 'accuracy' of responsibility attributions. This argument is in line with other studies' findings of media effects on EU policy preferences (Meltzer et al 2020), but also more general findings that visibility of the EU, its institutions, and processes in the news media can influence opinions and knowledge about the EU (Clark 2014;de Vries et al 2011;Marquart et al 2019;Semetko, van der Brug, and Valkenburg 2003). In detail, we expect that higher EU media visibility in a certain policy area results in stronger citizens' attribution of policy responsibility to the EU.…”
Section: Rq1: Are Media Effects On Policy Responsibility Attribution supporting
confidence: 91%
“…For the actual expectation of a media effect on the individual level, we follow the straightforward argument by Hobolt and Tilley (2014) that news media can have effects on responsibility beyond framing, and in particular on the 'accuracy' of responsibility attributions. This argument is in line with other studies' findings of media effects on EU policy preferences (Meltzer et al 2020), but also more general findings that visibility of the EU, its institutions, and processes in the news media can influence opinions and knowledge about the EU (Clark 2014;de Vries et al 2011;Marquart et al 2019;Semetko, van der Brug, and Valkenburg 2003). In detail, we expect that higher EU media visibility in a certain policy area results in stronger citizens' attribution of policy responsibility to the EU.…”
Section: Rq1: Are Media Effects On Policy Responsibility Attribution supporting
confidence: 91%
“…Sophistication might then equal variation, in the sense that detailed knowledge about the EU facilitates the formation of more crystallised (positive as well as negative) opinions. Although intuitively one might expect a better EU knowledge to be related to higher support of European integration (as shown by, e.g., Janssen 1991), several studies have shown that 'knowing' about the EU does not necessarily lead to 'loving' the EU (e.g., Karp et al 2003;Marquart et al 2019).…”
Section: Specific Eu Policies and The Role Of Political Sophisticationmentioning
confidence: 99%
“…This observation also extends to knowledge acquisition. In particular, there is a positive relationship between media use and knowledge about politics (Becker & Whitney, 1980;Marquart et al, 2019;McLeod & McDonald, 1985) or climate change (Stamm et al, 2000;Taddicken & Neverla, 2011;Zhao, 2009). Thus, the higher the media use, the better the actual knowledge about the given subjects.…”
Section: Media Use In Times Of Crisesmentioning
confidence: 99%